Boldine Ameliorates Estrogen Deficiency-Induced Bone Loss via Inhibiting Bone Resorption - Chen, Kun; Lv, Zheng-tao; Cheng, Peng; Zhu, Wen-tao; Liang, Shuang; Yang, Qing; Parkman, Virginia-Jeni Akila; Zhou, Chen-he; Jing, Xing-zhi; Liu, Hui; Wang, Yu-ting; Lin, Hui; et al. (Frontiers in Pharmacology, 2018)
Osteoporosis is an enormous health problem caused by the imbalance between bone resorption and bone formation. The current therapeutic strategies for osteoporosis still have some limitations. Boldine, an alkaloid isolated from Peumus boldus, has been shown to have antioxidant and anti-inflammatory effects in vivo. For the first time, we discover that boldine has a protective effect for the estrogen deficiency-induced bone loss in mice. According to the Micro-CT and histomorphometry assays, boldine conducts this protective effect through inhibiting bone resorption without affecting bone formation in vivo. Moreover, we showed that boldine can inhibit receptor activator of nuclear factor κB ligand (RANKL)-induced osteoclast formation via impairing the AKT signaling pathways, while SC79 (an AKT agonist) partially rescue this effect. In conclusion, our results suggest that boldine can prevent estrogen deficiency-induced osteoporosis by inhibiting osteoclastogenesis. Thus, boldine may be served as a novel therapeutic agent for anti-osteoporotic therapy.